LncRNA NEAT1 Targets Fibroblast-Like Synoviocytes in Rheumatoid Arthritis via the miR-410-3p/YY1 Axis - Wang, Yuejiao; Hou, Linxin; Yuan, Xiaowei; Xu, Neili; Zhao, Shuai; Yang, Lili; Zhang, Ning (Frontiers in Immunology, 2020)
LncRNA NEAT1 functions as an oncogene in multiple human cancers. However, its expression and role in fibroblast-like synoviocytes (FLSs) from patients with rheumatoid arthritis (RA) remain unclear. Thus, we investigated the expression of NEAT1 in synovial tissues and FLSs in RA, to determine its role in the development of RA. Quantitative real-time polymerase chain reaction was used to measure the expression of NEAT1. FLS proliferation was evaluated using cell proliferation assays. Flow cytometry was used to analyze cell cycle progression and apoptosis in FLSs. Binding between NEAT1 and miR-410-3p was demonstrated by dual-luciferase assays. We found that NEAT1 was upregulated in synovial tissues and FLSs in RA. Upregulation of NEAT1 promoted cell proliferation, induced S-to G2/M phase transition, and suppressed apoptosis in RA FLSs. NEAT1 directly bound to and negatively modulated miR-410-3p expression, while positively regulating YinYang 1(YY1; a miR-410-3p target). Inhibiting miR-410-3p and upregulating YY1 partially restored the inhibitory role in cell viability induced by the depletion of NEAT1 in RA FLSs. Besides pro-proliferative and anti-apoptotic roles, upregulation of NEAT1 promoted migration, invasion, and inflammatory cytokines secretion in RA FLSs. Taken together, our results suggest that the NEAT1 may serve as a novel diagnostic and therapeutic target for patients with RA.